Fighting Women of Kabuki Theater and the Legacy of Women’s Japanese Martial Arts - Klens-Bigman, Deborah (Revista de Artes Marciales Asiáticas, 2012)
The fighting woman character has been a staple of Japan’s kabuki theater almost since its inception. Audiences accepted these characters, especially fighting women of the samurai class, as part of the depiction of Edo period (1603–1868) life. This paper explores several of these characters and suggests that they help form the legacy of women’s practice of martial arts today.